Congregational Care: Philosophical Reflection on a Case Study - Bellous, Joyce Edith (Religions, 2023)
Congregational care strengthens relationships and supports spiritual growth. This article establishes groundwork for developing congregational care at First Baptist in Edmonton (FBC) by introducing a spiritual needs approach to engage people in conversation and by using a Spiritual Styles Assessment that has 36 questions to foster communication among congregational members. The article has four parts. The first introduces the congregation and a list of spiritual needs. The second part includes information about the Spiritual Styles Assessment and spirituality research. Parts three and four describe attitudes, skills and practices that enhance communicative action by helping people talk together and practice radical welcome as a foundation for congregational care. The purpose for establishing a foundation for congregational care is to suggest a way forward for a congregation that faces significant differences in values, beliefs, expectations, personal experience, and faith assumptions, even among people who have known each other for years. FBC is trying to find ways to reach understanding and offer care to all who enter the Sanctuary. The purpose of the article is to reflect philosophically on what congregants need from each other as signs of respect, inclusion and caring. The article outlines attitudes, skills, and practices that create communicative communities that are capable of nurturing congregational care by developing human understanding based on faith experience and communicative action.